Mechanical Property Characterisation of Electron Beam Melted (EBM) Ti-6Al-4V via Small Punch Tensile Testing - Robert Lancaster (Key Engineering Materials, 2017)
Small punch (SP) tensile testing provides several advantages over conventional test techniques for mechanical property characterisation of components produced using novel manufacturing processes. Additive layer manufacturing (ALM) is becoming more widespread, particularly in high value manufacturing sectors such as the gas turbine industry as it allows near net shape manufacture of near fully dense components with complex geometries. One such ALM process which is receiving attention from the gas turbine industry is electron beam melting (EBM), a powder bed process which uses an electron beam energy source. The additive nature of ALM processes including EBM results in the microstructures produced differing significantly to those produced by conventional processing techniques. As well as being influenced by the input parameters, the microstructure and hence mechanical properties are also affected by the geometry of the component being manufactured, primarily due to the effect this has on the cooling characteristics. SP testing of material manufactured by EBM allows the mechanical property characterisation of local component representative geometries which wouldn’t be possible using conventional uniaxial testing techniques. This work is aimed towards developing and validating the SP tensile technique for this application; different Ti-6Al-4V material variants manufactured using EBM as well as conventional methods have been characterised with a range of test conditions.